THE ROUTINE MAINTENANCE PLANNING CONSULTANCY FOR PANGKAH KULON - BOOLO ROAD, LOCATION: UJUNGPANGKAH DISTRICT, GRESIK REGENCY - Khakimin, Achmad Lukmanul; Witjaksana, Budi; Tjendani, Hanie Teki (Transpublika Publisher, 2022)
Road infrastructure is the lifeblood of a region's economy because it connects and increases the movement of people and goods. Traffic jams in the city of Gresik fall into the severe category. This is evidenced by the long queues of vehicles and the time it takes to decompose traffic jams for hours. The Gresik Regency Government, through the Highways Public Works and Water Resources Office, needs to carry out systematic and appropriate planning to overcome the above problems. Maintenance is carried out by preparation, topographic survey, traffic survey, and then the calculation of the pavement plan. From the analysis results obtained CBR subgrade = 3%; DDT = 4; IP = 2.5; FR = 1.0; LER = 2.18; ITP = 9.5; Ipo = 3.9 – 3.5. After the calculations, we obtained a 10 cm asphalt surface layer (4 cm ACWC, 6 cm ACBC) and 20 cm CTB fill for leveling.